2008
DOI: 10.1038/nature06561
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle control of centromeric repeat transcription and heterochromatin assembly

Abstract: Heterochromatin in eukaryotic genomes regulates diverse chromosomal processes including transcriptional silencing. However, in Schizosaccharomyces pombe RNA polymerase II (RNAPII) transcription of centromeric repeats is essential for RNA-interference-mediated heterochromatin assembly. Here we study heterochromatin dynamics during the cell cycle and its effect on RNAPII transcription. We describe a brief period during the S phase of the cell cycle in which RNAPII preferentially transcribes centromeric repeats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
433
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(468 citation statements)
references
References 29 publications
34
433
0
1
Order By: Relevance
“…This is consistent with studies of the role of transcription and RNAi in centromere activity in S. pombe (Volpe et al, 2002(Volpe et al, , 2003Chen et al, 2008); however, the role for transcription in metazoan kinetochore activity has been little studied (Saffery et al, 2003;Fukagawa et al, 2004;Wong et al, 2007;Chueh et al, 2009). Our previous studies found that alphoid tetO kinetochore inactivation by the tTS correlated with the recruitment of heterochromatin protein HP1␣ and that direct recruitment of HP1␣ as a TetR:EYFP fusion protein could also inactivate the kinetochore (Nakano et al, 2008).…”
Section: Molecular Biology Of the Cell 4200supporting
confidence: 77%
See 1 more Smart Citation
“…This is consistent with studies of the role of transcription and RNAi in centromere activity in S. pombe (Volpe et al, 2002(Volpe et al, , 2003Chen et al, 2008); however, the role for transcription in metazoan kinetochore activity has been little studied (Saffery et al, 2003;Fukagawa et al, 2004;Wong et al, 2007;Chueh et al, 2009). Our previous studies found that alphoid tetO kinetochore inactivation by the tTS correlated with the recruitment of heterochromatin protein HP1␣ and that direct recruitment of HP1␣ as a TetR:EYFP fusion protein could also inactivate the kinetochore (Nakano et al, 2008).…”
Section: Molecular Biology Of the Cell 4200supporting
confidence: 77%
“…That centromere is inactivated by being bombarded by transcription from an adjacent strong promoter. Thus, it is not suited for the analysis of the effects of transcriptional repressors on centromere function, a key question, given the demonstrated role of transcription in centromere function in Schizosaccharomyces pombe (Volpe et al, 2002(Volpe et al, , 2003Chen et al, 2008). Furthermore, in its inactive state, the budding yeast conditional centromere was reported to be fully occupied with CENP-A/Cse4 (Collins et al, 2005), although this was disputed (Mythreye and Bloom, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…From studies across major eukaryotic lineages, it is clear that PCTs have other roles in addition to heterochromatin formation and that some of these functions may be strand specific (Chen et al 2008;Eymery et al 2009a;Probst et al 2010). Recent research suggests that PCTs may play a role in the formation of chromocenters (Eymery et al 2009a;Probst et al 2010), nuclear structures formed from the aggregation of heterochromatin from multiple chromosomes.…”
Section: Pericentric Transcriptionmentioning
confidence: 99%
“…1a, b) and performs a variety of functions such as maintaining the boundary that separates the euchromatin from the centromere core (Chen et al 2008), providing sites for sister chromatid cohesion during mitosis (Lippman and Martienssen 2004), and repressing meiotic recombination around the centromere (Ellermeier et al 2010). Transcripts emanating from this region, known as pericentric transcripts, or PCTs, recruit heterochromatin factors that maintain the heterochromatic histone modifications, specifically H3K9me2, H3K9me3, H3K27me2, and H3K27me3 (Lippman and Martienssen 2004;Chen et al 2008;Djupedal et al 2009;Reyes-Turcu et al 2011).…”
Section: Pericentric Transcriptionmentioning
confidence: 99%
“…L'assemblage de CENP-A, si important pour la formation du kinétochore, dépend aussi de ces siARN [8]. Ces répétitions centromériques sont exprimées transitoirement au cours de la phase S, suggérant une régulation dynamique, dépendante du cycle cellulaire, des niveaux d'expression des ARN non-codants [9]. Les centromères chez les eucaryotes supérieurs produisent aussi des ARN non-codants ( Figure 1A) [10][11][12] qui ne sont apparemment pas associés à la production de siARN.…”
Section: Dynamique Transcriptionnelle De L'hétérochromatineunclassified